Biogas generation by hybrid treatment of dairy wastewater with lipolytic whole cell preparations and anaerobic sludge - Ferreira, Tainá F.; Santos, Patrick A.; Paula, Ariela V. [UNESP]; de Castro, Heizir F.; Andrade, Grazielle S.S. (Elsevier, 2021)
This study aimed to assess the potential of the biochemical methane production and biodegradability of dairy wastewater employing a hybrid treatment: granular anaerobic sludge as inoculum and whole cells of Penicillium citrinum with high lipase activity. It was expected that mycelium-bound lipase from whole cells would enhance hydrolysis, contributing to the efficiency of anaerobic digestion by granular inoculum. Seven substrate and microbial combinations were prepared; five contained the inoculum and whole cells cultivated in different agroindustrial wastes and two were controls (inoculated and uninoculated). A synergistic microbial interaction was evidenced by the high cumulative methane production after 45 h of reaction, reaching 231 mL g−1 volatile solids. pH was maintained at values near neutrality in all treatments, and chemical oxygen demand removal ranged from 42 to 57 % in hybrid treatments. First-order and modified Gompertz kinetic models were fitted to experimental data, and a lag phase was not observed. The results show the potential of hybrid treatment of dairy wastewater with whole cells produced in waste-based media for biogas production.
Keywords: Biogas; Dairy wastewater; Lipase; Penicillium citrinum; Whole cell